1995
DOI: 10.1038/ng1095-191
|View full text |Cite
|
Sign up to set email alerts
|

Long–term hepatic adenovirus–mediated gene expression in mice following CTLA4Ig administration

Abstract: Recombinant adenovirus vectors are efficient at transferring genes into somatic tissues but are limited for use in clinical gene therapy by immunologic factors that result in the rapid loss of gene expression and inhibit secondary gene transfer. This study demonstrates that systemic coadministration of recombinant adenovirus with soluble CTLA4Ig, which is known to block co-stimulatory signals between T cells and antigen presenting cells, leads to persistent adenoviral gene expression in mice without long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
186
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(193 citation statements)
references
References 29 publications
6
186
1
Order By: Relevance
“…However, Tripathy et al 34 reported that the expression of endogenous proteins in animals lessens the development of their immunorejection. Kay et al 35 demonstrated, furthermore, the effect of CTLA4Ig, a costimulatory signal inhibitor between T lymphocytes and antigen-presenting cells. With the use of CTLA4Ig, persistent adenoviral gene expression was obtained in mice without long-term immunosuppression.…”
Section: Correspondence: T Takeuchi Department Of Molecular Medicinementioning
confidence: 99%
“…However, Tripathy et al 34 reported that the expression of endogenous proteins in animals lessens the development of their immunorejection. Kay et al 35 demonstrated, furthermore, the effect of CTLA4Ig, a costimulatory signal inhibitor between T lymphocytes and antigen-presenting cells. With the use of CTLA4Ig, persistent adenoviral gene expression was obtained in mice without long-term immunosuppression.…”
Section: Correspondence: T Takeuchi Department Of Molecular Medicinementioning
confidence: 99%
“…General immune suppression may be induced in mice by inhibiting the CD28-B7 costimulatory signals by systemic administration of a recombinant chimeric protein, CTLA4-Ig, which consists of an immunoglobulin fused to CTLA4. 32 Kay et al 33 have demonstrated, in mice, that administration of muCTLA4-Ig, consisting of murine immunoglobulin C␥2a fused to murine CTLA4, extends the duration of adenovirus-mediated gene expression in the liver. They have also recently demonstrated that constitutive expression of murine CTLA4Ig from the viral vector also prolongs transgene expression.…”
Section: U Adrl In Pbs) the Results Indicate Transduction Of Rpe Cementioning
confidence: 99%
“…However, most of them present secondary complications and/or their use in human patients is questionable. These strategies include macrophage depletion, 39,40 use of immunosuppressive agents (cyclosporin A, cyclophosphamide, dexamethasone, FK506, Interleukin-12 and deoxypergualin), [41][42][43][44][45][46] use of antibodies to deplete CTLs, 47,48 blockade of costimulatory interactions between APCs, T and B cells, [49][50][51][52] intrathymic administration of adenovirus, 53 oral tolerization, 54 use of vectors derived from non-crossreacting serotypes, 55,56 use of adenoviruses from other species 57,58 and coating vectors with inert chemicals like polyethylene glycol (PEG). [59][60][61] Diverse in vivo studies in mice suggested that, in the absence of an immune response, first-generation adenoviral vector DNA is maintained as a stable episome in the host cell.…”
Section: Gutless Adenovirus and Immune Responsementioning
confidence: 99%